Temporal Variation of the Presence of Rhodnius prolixus (Hemiptera: Reduviidae) Into Rural Dwellings in the Department of Casanare, Eastern Colombia (2020)
Rhodnius prolixus (Stål, 1859) is the major vector of Trypanosoma cruzi in Colombia and Venezuela. The species is strongly associated with high-altitude ecotopes, such as sylvatic palms (Attalea butyracea), where spatially and temporally stable infestations are established. We investigated temporal variation in regards to the presence of R. prolixus in rural dwellings in the department of Casanare (eastern Colombia) over a period of 12 mo. Thirty houses were sampled from January to December 2017 by installing Maria sensors, collecting triatomines through community entomological surveillance, and conducting a monthly search in each house. The collection of specimens from the houses varied significantly by month with the higher number of collections occurring in the low-rainfall season and the lower number of collections occurring in the months of increased precipitation. The proportions of males, females, and nymphs also varied significantly throughout the time period: nymphs (fifth instar only) were reported only during May, July, and September and significantly greater numbers of females than males were reported in the inspected dwellings in all months. Density, crowding, and colonization indices varied according to the season. A bloodmeal analysis revealed 17 different hosts. A total of 42 randomly selected R. prolixus specimens were subjected to molecular analyses for detection of T. cruzi DNA with 22 found positive (infection prevalence of 52%). In conclusion, we observed a high presence of R. prolixus (infected with T. cruzi) in dwellings close to native palm plantations. These findings indicate a high risk of vector transmission of T. cruzi for people in the study areas and challenges for the current vector control schemes in the region. © The Author(s) 2019. Published by Oxford University Press on behalf of Entomological Society of America. All rights reserved. For permissions, please e-mail: journals.permissions@oup.com.